Pre-texts for the Rawlsian Theory of Justice (2016)
The objective was established the first concepts or the first forms before they were located substantially in John Rawls’s masterpiece: A Theory of Justice. It was the central idea in this dossier. The contractual rawlsians documents were reviewed critically and were found such concepts: “Justice as Fairness” (1958), “The Sense of Justice” (1963) y “Distributive Justice” (1973). These germinal ideas were found such as the rejection of the criterion of utility, the fist formulation of the principles of justice, the problematic of moral subject and its obligation with compliance with regulations given by the principles of justice, and finally the veil of ignorance. Perhaps themselves have rejected some criticisms of Rawls.